Utilization of Sugarcane Bagasse Waste for Eco-Friendly Roofing: Synergy of Agrowaste Management and Sustainable Architecture - A.A Sihombing, Ranjiv; M. Ahleyani; Pintu Batu, Aprilda Friana; Kurniawan Pratama, Andre; Simanjuntak, Keisha Dwipa (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Sugarcane bagasse in Indonesia represents an underutilized resource, with East Java producing 1,132,963 tons in 2021. This study explores its potential as eco-friendly roofing through Sugarcane-Inspired Roofing (SIR). A descriptive method was applied, including literature review, material analysis, experimental testing of SIR’s durability and efficiency, and SWOT analysis. Results showed that SIR has good waterproof qualities, strength, and potential for large-scale production (9,000 units/month) with local materials. Field testing demonstrated environmental benefits, economic feasibility, and market acceptance as a sustainable roofing material. In conclusion, SIR is viable for supporting sustainable construction and reducing agrowaste. Future research should focus on improving material composition and expanding market adoption.